2009
DOI: 10.1016/j.brainres.2009.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Impaired axonal transport and neurofilament compaction occur in separate populations of injured axons following diffuse brain injury in the immature rat

Abstract: Diffuse brain injury is a leading cause of mortality in infants and children under 4 years of age and results in cognitive deficits in survivors. The anatomic basis for these behavioral deficits may be traumatic axonal injury (TAI), which manifests as impaired axonal transport (IAT) and neurofilament compaction (NFC), and may occur as a result of glutamate receptor activation. The extent of IAT and NFC was evaluated at 6, 24 and 72 hours following non-contusive brain trauma in the 17 day-old rat to examine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 40 publications
(72 reference statements)
2
46
0
1
Order By: Relevance
“…In humans as well as in animals morphologic changes in NF occur in DAI following TBI. In animals those changes are observed in sites of contusions, accompanied by selective necrosis of neurons in the brain cortex, especially in the hippocampus which is exceptionally susceptible to hypoxia and several other damaging factors [3,5,10,16,19,20,[22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans as well as in animals morphologic changes in NF occur in DAI following TBI. In animals those changes are observed in sites of contusions, accompanied by selective necrosis of neurons in the brain cortex, especially in the hippocampus which is exceptionally susceptible to hypoxia and several other damaging factors [3,5,10,16,19,20,[22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…In majority of studies, NF-H and NF-L were researched [3][4][5]7,10,12,15,16,19,20,23,28]. Neurofilaments at the site of the brain contusion disintegrate, their complete disappearance was observed 1 to 2 weeks following trauma [10,20,22,26].…”
Section: Discussionmentioning
confidence: 99%
“…We had based our study design on previous in vitro and in vivo preclinical studies in adults. [62][63][64][65] In our initial ageappropriate monotherapy conformational studies with FK506, however, we found that when FK506 was administered IP as a monotherapy immediately and 6 h after TBI at doses of 10 or 25 mg/kg, the signature dephosphorylation of neurofilaments and axonal degeneration 66 was significantly reduced, but benefits were achieved only at doses that were 2-5 times greater than in the adult [62][63][64]67 ; there was no amelioration of impaired axonal transport or CAP deficits. 59 Ultimately, because FK506 failed to improve functional outcome associated with persistent CAP deficits in the white matter tracts after diffuse trauma to the immature brain, we abandoned the idea of using this medication for our combination therapy; instead, we evaluated minocycline and GPE.…”
Section: Concurrent Targeted Therapy Combination: Glypromate and Minomentioning
confidence: 87%
“…U ludzi i zwierząt z TBI zmiany morfologiczne w obrębie NF występowały w przypadkach wspomnianego już powyżej rozlanego uszkodzenia aksonów, a u zwierząt także w ogniskach stłuczenia mózgu, współistniejących z wybiórczą martwicą neuronów w korze mózgu, a zwłaszcza w hipokampie, okolicy szczególnie wrażliwej zarówno na epizody hipoksji, jak i szerokie spektrum czynników uszkadzających [10][11][12][13][16][17][18][19][20][21][22][23][24].…”
Section: Myszy śWinie Koty) W Większości Przypadków Badano Podjednunclassified
“…In people and animals with TBI, morphological changes within NF have been found to occur in cases of the above-mentioned diffuse axonal injury, an in animals also in brain contusion foci, coexisting with selective neuronal necrosis in the brain cortex and, particularly, in the hippocampus -a region which is especially sensitive both to hypoxic episodes and to a wide spectrum of damaging factors [10][11][12][13][16][17][18][19][20][21][22][23][24].…”
Section: Badania Na Materiale Ludzkimmentioning
confidence: 99%